Catalyst Asia Issue 05 - Institute for Societal Leadership, (Institutional Knowledge at Singapore Management University, 2017)
STORIES FROM THE GROUND Grow A Forest In Your Mind The Volunteer Bank A Labour of Love The Art of Helping Others It Takes A Village Fit For Life The People's Doctor Planting Big Trees in Everybody's Hearts Organic Rice Revolution Lighting Up Lives INSIGHTS FROM THE INSIDE A Lifesaving Journey A Pen For The Blind Battling the Transport System The Mentor and Inspirer of Social Change Caring For Migrants Road Safety Advocates Consumer Protection in the Digital Age The Rescue Squad The Hero and Sidekick A Hybrid Profile of Social Entrepreneurship